High‐Affinity Carbohydrate Binding by Trimeric Benzoboroxoles Measured on Carbohydrate Arrays. Issue 16 (10th September 2014) - Claes, Dorith; Memmel, Elisabeth; Holzapfel, Malte; Seibel, Jürgen; Maison, Wolfgang
Abstract Carbohydrates are involved in a wide range of biological processes of pharmaceutical relevance. The selective recognition of carbohydrates is therefore of great interest in biology and medicine. In this study we present the synthesis of fluorescent multimeric benzoboroxoles and the analysis of multivalent binding processes to immobilized carbohydrate arrays by fluorescence spectroscopy. We observed high binding affinities of trimeric benzoboroxoles by determination of KDsurf values for their interaction with α‐Gal on glass chips. The observed KDsurf values were in the mid‐nM range (49 and 104 nM) and are comparable to the KDsurf values for binding of natural lectins, such as that of ConA to immobilized α‐Man (79 nM). The array technology was found to be an excellent tool for studying the binding processes of multivalent lectin mimetics with respect to profiling and quantitation.